Off-farm and on-farm entrepreneurship development for improving rural economy - Agrawal, K P (Indian Farming, 2015)
With increasing family size of the farmers and fragmentation of land possessed by them, puts these farmers under pressure to take loans for their day to day needs and agriculture. Within a span of time these farmers come under huge debt as they are unable to repay their loans whether to banks or the money lenders. For sustainable agriculture it is suggested that the villages become self-reliant and develop some kind of enterpreneurship in various areas like, processing and value-addition of farm produce, marketing, storage and preservation of farm produce to name a few. Further, reorientation of agricultural education is also required so as to develop self confidence in agricultural graduates for enterpreneurship and skills in areas like agri- business, processing and value addition, natural resources management etc.